Breadth, Depth and Form? Pitching Constitutional Law Content in the Classroom - Sarah Murray (Legal Education Review)
In a response to what she viewed as a crisis in education, Hannah Arendt described education as requiring nothing less than ‘the renewal of our common world’: Education is the point at which we decide whether we love the world enough to assume responsibility for it and by the same token save it from that ruin which, except for renewal, except for the coming of the new and young, would be inevitable. Arendt connects education to broader public goals. For some disciplines, such lofty aspirations might seem unobtainable, and even irrelevant, to the teaching enterprise. However, in law, and in public law particularly, the broader goals of education align clearly with our pedagogical mission.